Analysis of the Service Level of Wamena Class 1 Airport Terminal Facilities in Jayawijaya Regency - Ayub Tanudy (International Journal of Economics (IJEC), 2023)
Jayawijaya Regency has one domestic airport, which is in Wamena City, called Wamena Airport. Therefore, the service standards and facilities provided by the airport management must be in accordance with standards that are able to create a comfortable and conducive atmosphere for airport service users. This research aims to find out the service level of Wamena Class 1 Airport Terminal Facilities in Jayawijaya Regency. This research uses data analyzed from Surfey which consists of 1 (one) variable, namely Airport Terminal Facility Services with indicators which include facilities in the passenger departure and arrival process, facilities that provide comfort to passengers and facilities that provide added value. The number of samples used was 123 people. The data analysis technique used is score analysis. The Surfey results show that the respondents' responses from the surfey passenger results were as follows: those who said they were very satisfied with a score of 55, those who were satisfied were 280, less satisfied at 120 and dissatisfied at 4. So the score regarding passenger inspection was 459 and was in the satisfied category.